Penggunaan Media Audio Visual untuk Meningkatkan Minat Belajar: Study Literature - Juliana Margareta Sumilat; Lady Carolina Pangalo (Journal on Education, 2024)
This study discusses the use of audio-visual media in increasing students ' learning Interest, Based on the study of relevant literature. Audio visual Media, has been shown to be effective in attracting students ' attention and increasing learning motivation. Various studies show that the application of this medium in the classroom not only makes learning materials more interesting but also helps students understand concepts better. The methodology used in this study is the study of literature to determine the impact of audio-visual media. The conclusion of this study emphasizes the importance of audio-visual media integration in the learning process to achieve optimal learning outcomes and increase overall student engagement.